Educação de jovens e adultos: fragmentos de práticas ou práticas em fragmentos? - Jensen, Janice Machado dos Santos (2008)
The objective of the present study is to be aware with the history of the Educação de Jovens e Adultos [Young and Adult people Education] (EJA) and to evidence the influence of the life history and academic study in the educators' school practices. A bibliographical study was accomplished allied to the methodology of the Oral History where three educators of young and adult people narratives were valued, in which some were emphasized issues about their actions in classroom. Therefore, the importance of this work is justified by the fact that it provides reflections and analyses on the history of the Educação de Jovens e Adultos (EJA) and about the educators' education in the intention of noticing the efficiency and effectiveness of the actions by reviewing that theme. The EJA is a practice as old as the mankind s history, although only recently has been studied as an object and scientific research. Moreover, the course in the history showed that many were the initiatives related to for young and adults education and the collaborators' speeches mapped scenery is still fragile in relation to the educator's graduation. A transition period is faced in the Modernity when uncertainties, fluidity and changes are part of the daily life. Thus, it was noticed that EJA is part of that process and as such, it is still under construction and qualification in the theories, projects, school practices and of affirmation in relation to the space it has been placed in the Education in our country. Keywords: Education; History; Young and Adult people, Graduation.